2009
DOI: 10.1073/pnas.0904984106
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Identification of an RNA-dependent RNA polymerase in Drosophila involved in RNAi and transposon suppression

Abstract: The authors wish to note the following: "In our article, we reported that recombinant subunit 1 of the Drosophila elongator complex, D-elp1, had RNA-dependent RNA polymerase (RdRP) activity and was involved in RNAi, transposon suppression, and endo-siRNA production, but not miRNA targeting. RdRP activity was identified using three assays to interrogate the reaction products: Dcr2 digestion, RNase sensitivity, and nearest neighbor analysis. Although we do see differential Dcr2 cleavage and RNase resistance, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…In some organisms, this results in the formation of new dsRNA, which is processed by Dicer into secondary siRNAs; in other organisms, Dicer is not involved in the amplification step and the RdRP is thought to synthesize single-stranded secondary siRNAs directly. Although only a subset of eukaryotes (including Schizosaccharomyces pombe, Neurospora, Caenorhabditis elegans and plants) encode an obvious RdRP enzyme in their genomes, several other animal species were recently found to posses RdRP activity mediated by divergent enzyme complexes (Lipardi and Paterson, 2009;Maida et al, 2009). This suggests that amplification of siRNAs is potentially more widely conserved than the conservation of the RdRP enzyme suggests.…”
Section: Introductionmentioning
confidence: 99%
“…In some organisms, this results in the formation of new dsRNA, which is processed by Dicer into secondary siRNAs; in other organisms, Dicer is not involved in the amplification step and the RdRP is thought to synthesize single-stranded secondary siRNAs directly. Although only a subset of eukaryotes (including Schizosaccharomyces pombe, Neurospora, Caenorhabditis elegans and plants) encode an obvious RdRP enzyme in their genomes, several other animal species were recently found to posses RdRP activity mediated by divergent enzyme complexes (Lipardi and Paterson, 2009;Maida et al, 2009). This suggests that amplification of siRNAs is potentially more widely conserved than the conservation of the RdRP enzyme suggests.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, these SID1-like proteins channel double-stranded RNAs (dsRNAs) between cells, enabling systemic spread of the silencing signal (1). Although a canonical invertebrate RNA-dependent RNA polymerase (RdRP) homologue has not yet been described, there is evidence that such RdRP activity may occur via other enzymes, leading to amplification of the silencing signal in insects (26).…”
mentioning
confidence: 99%
“…In D. melanogaster it has been shown that systemic spread of the RNAi response is essential for an efficient antiviral response and components of the dsRNA uptake machinery have been identified [60,98]. To date no protein with RNA-dependent RNA polymerase (RdRP) activity for amplification of small RNAs has been identified in insects [72,73]; however, it was proposed that reverse transcription of viral RNA by retrotransposons may result in viral cDNA elements serving as a template for the generation of new viRNAs [39]. In U4.4 cells it has been shown that siRNAs can spread through the culture if there is cell-to-cell contact, but cannot spread freely through the culture medium [6].…”
Section: Mirnasmentioning
confidence: 99%